Phenomenon of Functional Homonymy in Ossetian Language - L. B. Morgoeva (Научный диалог, 2023)
The phenomenon of homonymy in the Ossetian language is considered as one of the complex and multi-aspect problems in Ossetian linguistics and in general linguistic theory. The lack of special works in Ossetian studies makes it relevant to consider this phenomenon in the context of functional homonymy. It is emphasized that the factors complicating the process of studying the conditions of emergence and functioning of homonyms in language and speech are the semantic intersections with polysemy, grammatically diverse “unpredictability”, functional variability, and as a result, the presence of various classifications and definitions within homonyms. An overview of the most well-known classifications of homonyms, analysis of lexicographical sources and literary texts has been made. As a result, the main criteria for “recognizing” functional homonyms have been identified and their differentiation from lexicalgrammatical homonyms in the Ossetian language has been carried out. The analysis has shown a number of difficulties in identifying functional homonyms. The author concludes that morphological instability and the syntactic functions of a word in a sentence can change its semantics, thus transferring it from one type of homonym to another. At the same time, it is noted that the main etymological principle of distinguishing homonyms may be ineffective when considering a larger number of parts of speech.